Application of Data Mining on Mobile Phone Sales Data Using the Apriori Algorithm (Case Study: Sentral Phone Store) - Maida Indrayani; Muhammad Iqbal (Journal of Information Technology, computer science and Electrical Engineering, 2025)
Mobile Phone is an electronic device used to communicate, transact digitally and as a medium for exchanging data and information. Mobile Phone is one of the secondary needs that must be owned by the community. In its development, there are various types of mobile phone brands that are sold and the prices offered also vary. The community can buy mobile phones according to their needs and financial capabilities. To see the mobile phone brands that are most in demand by the community, data mining is used using the apriori algorithm to analyze the sales of the most sold mobile phones. So that with the use of the apriori algorithm, it avoids the accumulation of unsold mobile phones.